The role of vagus nerve stimulation in modulating Parkinson’s disease via the microbiota-gut-brain axis: a comprehensive review - Yang, Lingqing; Fan, Shiyu; Sun, Li; Han, Jingru; Wang, Meng; Yu, Tao (Frontiers in Neurology, 2025)
As the global aging trend intensifies, the incidence of neurodegenerative diseases, including Parkinson’s disease (PD), is increasing year by year. Currently, there is no effective cure for PD. Therefore, exploring safe and effective therapeutic targets is of utmost importance. Previous studies have shown that modulation of vagus nerve (VN) activity, a key communication pathway between the brain and the gut, may produce therapeutic effects in PD and influence its disease course by regulating the gut microbiota, brain plasticity, neuroimmune, and neuroendocrine systems, while the nerve itself also plays a complex role that can contribute to pathological processes like disease propagation. This review comprehensively summarizes the potential mechanisms by which vagus nerve stimulation (VNS) intervenes in PD may influence the microbiota-gut-brain axis (MGBA), including the regulation of gut microbiota composition and metabolites, inhibition of central and peripheral neuroinflammatory responses, modulation of hypothalamic–pituitary–adrenal (HPA) axis function, enhancement of brain region functional connectivity and neurotrophic factor secretion, and explores its potential value in translating into clinical therapeutic strategies. This study is the first to integrate the MGBA theory with VNS technology, revealing its cross-system regulatory network in intervening PD and providing new ideas for breaking through the limitations of traditional treatments.